KEPATUHAN KONSUMSI TABLET FE DALAM MENCEGAH ANEMI GIZI BESI PADA IBU HAMIL DI WILAYAH PUSKESMAS KECAMATAN JAKARTA PUSAT - Sugeng Triyani (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Departement Program in giving pregnant mothers Fe pills is one of forms to the prevent iron anaemia deficiency in pregnantcies to prevent anaemia. In Indonesia prevalency iron nutrient anaemia in pregnantcy is still high abaut 37,1% (RISKESDAS, 2013). On factor of it is the low desciplinende pregnant mother trimester III to consume Fe pills in Puskesmas Kecamatan Cempaka Putih seen the lownees of pregnant mothers descipline to consume Fe pills abaut 33,33% whereas in Puskesmas Kecamatan Sawah Besar is 58,3%.The aim of this research is to know ehether theres the deferentsce between education, science, information and family support with the descipline of pregnant mothers in comsumen Fe pills in Puskesmas Kecamatan Cempaka Putih and Sawah Besar.Methods : cross sectional study with 134 pregnant mothers trimester III. The results of the researchshowed that theres relationship between the discipline in consuming Fe pillswith status of anaemia deficiency iron (p = 0.027)in pregnant women. variabel education and family support as confounding.Pregnant mothers who do not discipline to consume Fe pills have chance to get anaemiadeficiency iron 4, 925 or 5 times compared with mothers have discipline to consume Fe pills up their being controled by variabel counselling and family supoprt.ith anaemia on pregnant mothers trimester IIIafter controlling variabel counselling and family support. The role of Midwife as the implementor of the programe give more priority in giving education and conseling abaut recovering iron nutrientanaemia on pregnant mothers . It is needed the family support be more pro active in preventing, promoting to over come in iron nutrient anaemia at pregnant mothers, to monitor pregnan mothers in keep their health and the fetus pregnant.